Interaksi Organisme Terhadap Perubahan Lingkungan: Studi Kasus Dalam Ekologi Hutan - Rosma Purba; Ruth Sahana Manalu; Tirza Grace Simamora; Meilinda Suriani Harefa (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
Ecology is a branch of biology that studies the relationship between living things and their habitats. Basically, living things depend on other living things or their habitats, so there is a reciprocal relationship between living things and other living things or their habitat. This relationship between organisms or their habitats is an interaction that can be in the form of predation, parasitism, commensalism, and mutualism. This study collected data through direct observation in the field. Mahogany is a semi-tolerant tree that is easy to grow and adapts well to various types of land, including beaches, teak forest edges, and even roadsides. Mahogany plants are often planted on the roadside as protective trees (Prasetyono, 2012). Mahogany has many advantages, because its wood, bark, sap and leaves are all available, and the interaction of biotic and abiotic factors with organisms greatly affects the growth of organisms. The relationship resulting from factors that occur in sonokeling trees, ketapang trees, mango trees and durian trees is an interaction between symbiotic symbiosis and parasitic symbiosis. Symbiosis Symbiosis is a relationship between two organisms where one benefits and the other is not harmed or benefited, that is, the interaction between durian trees and ferns and dragon scales. Parasite symbiosis is a relationship of two organisms in which one benefits and the other is harmed, that is, the interaction between mango trees and benalu.